The downside of omnichannel / Nor Amira Mohd Ali and Muhammad Hanif Abdul Gafar - Mohd Ali, Nor Amira; Abdul Gafar, Muhammad Hanif (Universiti Teknologi MARA, Kedah, 2022)
Media have announced numerous retail closures and bankruptcies, especially during the mid-Covid-19 attack, which has made businesspeople endure a difficult condition, people started to believe that retail was dying. They think there is no room for them to survive in the retail industry. However, the reality is that the current retail landscape is evolving at a fast pace and requires innovative business models to succeed. The rise of digital platforms has affected the routine activities of consumers as well as their purchase decision towards products or services. To stay competitive in the dynamic form of the market, retailers need to change and adapt various retailing strategies, such as from a single-channel strategy to an omnichannel strategy which is very popular in the retail business nowadays. Other than that, online shopping also has affected the dynamics of omnichannel retail, and technological innovation is taking retail to the next level (Bae and Deborah., 2020). Unfortunately, the downside of this strategy requires massive costs, experts in web programming, technology, and software, and a very strong data security system. Besides that, retailers still need to face an operational challenge caused by border restrictions and greater online competition between small and large companies. This has led to rising service standards and increasing consumer demand to optimise the omnichannel strategy. Hence, only large-scale business industries can implement this marketing strategy, but for small-scale businesses, this is too heavy a burden to bear.